Investigation of patulin and citrinin in grape must and wine from grapes naturally contaminated by strains of Penicillium expansum. (August 2018) - Ostry, Vladimir; Malir, Frantisek; Cumova, Martina; Kyrova, Veronika; Toman, Jakub; Grosse, Yann; Pospichalova, Marketa; Ruprich, Jiri
Abstract: Twenty three strains of Penicillium expansum, as a predominant species, were isolated from 23 (92%) out of 25 grape samples of 17 different grape varieties. The results of the identification of P. expansum strains were confirmed by a PCR method. Most of the isolates of P. expansum (21/23, 91%), when tested for toxigenicity, were bi-toxigenic: they produced citrinin (CIT) and particularly high amounts of patulin (PAT). A validated UPLC-MS/MS method for the determination of PAT and CIT was applied. The limits of quantification (LOQ) for PAT and CIT in grape must and toxigenicity testing samples were 100 and 2 ng/g, respectively. The results of PAT and CIT quantification in 23 grape must samples demonstrated the occurrence of PAT in 10 (43%) grape must samples (mean: 171 ng/g; median: 50 ng/g; and range: 143–644 ng/g) and the occurrence of CIT in two (9%) grape must samples (mean: 1 ng/g; median: 1 ng/g; and range: 2.5–3.5 ng/g). This is the first report on the natural occurrence of CIT in grape must. A validated HPLC-UV-VIS method for the determination of PAT in wine samples was applied, and concentrations in all 23 wine samples were below the LOQ (<10 ng/g). Highlights: Twenty three strains of Penicillium expansum were isolated from grape samples. Twenty one strains of Penicillium expansum were bi-toxigenic – producing patulin (PAT) and citrinin (CIT). PAT and CIT were quantified in grape must. This is the first report on the natural occurrence of CIT in grape must. These findings suggest that there is a potential risk of dietary exposure to PAT and CIT in the grape–wine chain.